Fishermen Home Based Business in The Settlement Of Bajo Tribe In Bajoe Village Of Tanete Riattang Timur Sub-District In Bone District - Novianti, Nur Asia; Umar, Ramli; Arfan, Amal (UNM Geographic Journal, 2017)
The research aimed to discover (1) the characteristics of the types of business of fishermen community in the settlement of Bajo Tribe in Bajoe Village, (2) the availability and the condition of facilities and infrastructures which supported the business activity of fishermen households in the settlement of Bajo Tribe in Bajoe Village, (3) the strategies which could be done to develop fishermen home based business in the settlement of Bajo Tribe in Bajoe Village. The research employed descriptive qualitative method. The targets of the research were Bajo Tribe community who opened home based business. The data were collected through observation, interview, and documentation techniques. The data were processed and analyzed by using descriptive analysis and SWOT analysis. The result of the research showed that (1) the characteristics of the types of fishermen home based business in the settlement of Bajo Tribe were dominated by business with sea products raw materials such as sea cucumber drying, fish, and shrimp drying as well as restaurants which the raw materials came from inside the settlement area and which the raw materials were not from sea products such as groceries seling, cakes and drink making, and services such as beauty shop; (2) the facilities and infrastructures which supported home based business activities in the settlement of Bajo Tribe were not yet fulfilled. To process the sea products, the product rooms were not yet available, the marketing was only to sell to regular customers, and the infrastructures for settlement garbage and waste were not yet available in all of the segments so it could not support home based business activities; (3) the strategies which could be done to developed home based business of fishermen households in the settlement of Bajo Tribe were by making the settlement area of Bajo Tribe as the center area of sea products processing so it would be better known by the people, developing the settlement of Bajo Tribe by managing the environment and making stalls as well as places to process the sea products so it could become the sales center of souvenirs of Bajo Tribe.